Cluster of Guillain-Barré Syndrome in Syrian coast (2016) (Latakia University Journal -Medical Sciences Series, 2022)
The research deals with the study of a group of emergency cases that fulfilled the criteria for diagnosing Guillain-Barré syndrome, which occurred in the form of a cluster during a certain period of time and a unified geographical location among patients.The research aims to know the clinical advantages of this group, as an attempt to develop a hypothesis that explains its occurrence